The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fphar.2016.00037
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold Proteins Regulating Extracellular Regulated Kinase Function in Cardiac Hypertrophy and Disease

Abstract: The mitogen activated protein kinase (MAPK)-extracellular regulated kinase 1/2 (ERK1/2) pathway is a central downstream signaling pathway that is activated in cardiac muscle cells during mechanical and agonist-mediated hypertrophy. Studies in genetic mouse models deficient in ERK-associated MAPK components pathway have further reinforced a direct role for this pathway in stress-induced cardiac hypertrophy and disease. However, more recent studies have highlighted that these signaling pathways may exert their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…However, its role in cardiac hypertrophy has yet to be investigated. Instead, other ERK-associated scaffolding proteins have been shown to play a central role in the maintenance of cardiomyocyte physiology and the induction of adaptive hypertrophy [40]. We have already mentioned β-arrestin as an important scaffold for ERK activation in response to GPCRs (see above).…”
Section: The Role Of Erk In Adaptive Cardiac Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation
“…However, its role in cardiac hypertrophy has yet to be investigated. Instead, other ERK-associated scaffolding proteins have been shown to play a central role in the maintenance of cardiomyocyte physiology and the induction of adaptive hypertrophy [40]. We have already mentioned β-arrestin as an important scaffold for ERK activation in response to GPCRs (see above).…”
Section: The Role Of Erk In Adaptive Cardiac Hypertrophymentioning
confidence: 99%
“…These proteins are myofilament-associated proteins highly induced during the hypertrophic process in mice and humans and are components of the sarcomere-associated biomechanical sensors. Loss of function studies highlighted that both proteins, FHL1 and ANKRD1, have detrimental roles in Gαq and phenylephrine-induced cardiac hypertrophy [40]. Fhl1 −/− hearts displayed a blunted response to pathological hypertrophy [48].…”
Section: The Role Of Erk In Adaptive Cardiac Hypertrophymentioning
confidence: 99%
“… 12 , 13 CBD administered directly into key brain regions reduces anxiety-like behavior in rodents. 14–16 CBD may also reduce anxiety and alleviate other neurological disorders by enhancing anandamide through fatty acid amide hydrolase inhibition 17 , 18 or by altering serotonergic (5-HT) neurotransmission, including actions as an indirect 5-HT1A agonist. 1 , 18–21 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, with regard to the enrichment results for hypertrophy, four out of the top nine functions related to the extracellular space were enriched in the sLDA-inferred markers. The authors of some previous studies have reported the relatedness between hypertrophy and the extracellular region of the heart, chondrocytes, and astrocytes [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. In particular, Yang et al [ 29 ] concluded that SCUBE3, which is an extracellular protein, may account for the accelerated onset and progression of cardiac hypertrophy.…”
Section: Resultsmentioning
confidence: 99%